Integrality of the therapeutic and pharmaceutical care: a necessary debate - Fabiola Sulpino Vieira (Universidade de São Paulo, 2017)
ABSTRACT The controversy surrounding the different interpretations on the integrality of therapeutic and pharmaceutical care has led to the delimitation of its scope by a law, but the issue has not been completely pacified. As a contribution to this debate, we aim to discuss the challenges to ensure the integrality of the therapeutic and pharmaceutical care, based on a conceptual approach on the meanings of integrality in the Brazilian Unified Health System (SUS). We identified important challenges to ensure the integrality of the therapeutic and pharmaceutical care in the SUS. These challenges are related to professional practices, the organization of actions and services, and the governmental response to health problems or to the treatment of specific population groups. For this end, governments need to carry out structuring actions and be efficient in using available resources so that existing problems can be overcome.